Synthesis and biological evaluation of N-biphenyl-nicotinic based moiety compounds: A new class of antimitotic agents for the treatment of Hodgkin Lymphoma. (31st March 2019) - Porcelli, L.; Stolfa, D.; Stefanachi, A.; Di Fonte, R.; Garofoli, M.; Iacobazzi, R.M.; Silvestris, N.; Guarini, A.; Cellamare, S.; Azzariti, A.
Abstract: We previously demonstrated that some N -biphenylanilides caused cell-cycle arrest at G2/M transition in breast cancer cells. Among them we choose three derivatives, namely PTA34, PTA73 and RS35 for experimentation in solid tumor cell lines, classical Hodgkin Lymphoma (cHL) cell lines and bona fide normal cell lines. Almost all tumor cells were sensitive to compounds in the nanomolar range whereas, they were not cytotoxic to normal ones. Interestingly the compounds caused a strong G2/M phase arrest in cHL cell lines, thus, here we investigated whether they affected the integrity of microtubules in such cells. We found that they induced a long prometaphase arrest, followed by induction of apoptosis which involved mitochondria. PTA73 and RS35 induced the mitotic arrest through the fragmentation of microtubules which prevented the kinethocore-mitotic spindle interaction and the exit from mitosis. PTA34 is instead a tubulin-targeting agent because it inhibited the tubulin polymerization as vinblastine. As such, PTA34 maintained the Cyclin B1-CDK1 regulatory complex activated during the G2/M arrest while inducing the inactivation of Bcl-2 through phosphorylation in Ser70, the degradation of Mcl-1 and a strong activation of BIML and BIMS proapoptotic isoforms. In addition PTA34 exerted an antiangiogenic effect by suppressing microvascular formation. Highlights: The discovery of N-biphenylanilides as a new class of microtubule-straightening compounds. N-biphenylanilides caused the mitotic cell death (MCD) in Hodgkin lymphoma cell lines and not in solid tumor cell lines. N-biphenylanilides are endowed with anti-angiogenic activity and are safe to normal cells.